Prevalence of hypertension and its associated risk factors among adults residing in urban slum: a population-based door-to-door study - Jain, Swati; Jain, Vikas (International Journal Of Community Medicine And Public Health, 2020)
Background: High blood pressure (HBP) is the single most common risk factor for disease burden all over world. In India, HBP has now emerged as a leading risk factor for morbidity and mortality. This study was carried out to find out prevalence of hypertension and its association with major risk factors among adults residing in urban slum. Methods: A population based door to door study was carried out in urban slum coming under field practice area of urban health training centre, Department of Community Medicine People’s College of Medical Sciences and Research Centre, Bhopal, Madhya Pradesh. Results: The mean systolic BP was 121.4 mmHg whereas mean diastolic BP was 79.4 mmHg. Overall, 64.6% respondents were normotensive, 15.4% were in the category of pre-hypertension, and 5% in stage 1 hypertension (HTN) and 15% were in stage 2 HTN, giving the overall prevalence of high blood pressure 20.07%. Conclusions: It can be concluded from present study that the prevalence of hypertension is quite high. Hence it is necessary to increase the public awareness about hypertension.